Determination of steel and lead bi-laminated shielding for military vehicles - Ary Machado de Azevedo; Domingos D'Oliveira Cardoso; Marcos Paulo Cavaliere de Medeiros; Sergio Gavazza; Rudnei Karam Morales (Brazilian Journal of Radiation Sciences)
In the present work, the transmission factors of γ-rays are determined in bi-layered shields composed of lead and steel, through a methodology composed of three distinct parts. The buildup calculation was performed using the methodology published by Broder in 1962 [1]. A computational simulation was used through a spherical model, a total of three concentric spheres were simulated, with the source in the center of the spheres. The first sphere represents the lead shield and its radius is represented by the thickness of this material. The second sphere represents the steel shield and its radius is the sum of the thicknesses of the shielding. The third sphere is the vacuum that will determine the number of photons that will pass. To verify if the analytical methodology can be used to calculate the transmission factor of the proposed shield, laboratory experiments were performed with the BGO (Bismuth Germanate) detector. Measurements were only made with the thickness of steel, and with 15 different thicknesses of lead, ranging from 0.11 cm to 2.01 cm, while keeping the steel thickness. Three different thicknesses of steel were used: 0.65 cm, 0.85 cm and 1.40 cm. The work is relevant in the field of radiological and nuclear defense, considering the application of this shield in military vehicles, and the efficiency of the proposed analytical methodology was demonstrated.